Expressing aspectual interactions in requirements engineering : experiences, problems and solutions - Fabry, Johan; Gordillo, Silvia Ethel (2010)
Aspect Oriented Requirements Engineering (AORE) provides support for modularizing crosscutting requirements. In the context of an industrial project in the domain of Slot Machines we needed to perform AORE, with a special emphasis on dependencies and interactions among concerns. We were however unable to find any report of large-scale industrial applications of AORE approaches that treat dependencies and interactions. We therefore evaluated two AORE approaches: Theme/Doc and MDSOCRE, to establish their applicability in our setting. In this paper we report on the limitations of both approaches we encountered and propose extensions that allow them to cope with concern interactions. We also show how these extensions provide the needed expressiveness by applying them to our industrial case study.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 01/07/2014)
EN: Science of Computer Programming, 78(1), pp. 65-92
Keywords: ESTUDIO DE CASOS